Renal pressure‐flow relationship and renin activation in a porcine model comparing unilateral and bilateral renal artery stenosis - Benny Drieghe; Gunther vanLoon; Sabrina Stuyvaert; Marc L. De Buyzere; Thierry Bové; Tine De Backer (Physiological Reports)
Abstract Because renal artery stenosis (RAS) often presents bilateral, we sought to investigate the renal pressure‐flow relationship and its relation to renin release, in the presence of a contralateral significant stenosis. A porcine model of graded unilateral RAS in the presence of a significant contralateral stenosis was created. The severity of the stenosis was expressed as the ratio between distal renal pressure (Pd) and aortic pressure (Pa). Pd and renal flow velocity were continuously measured using a combined pressure‐flow wire (Combowire®). Hemodynamic measurements and blood sampling for renin, angiotensin, and aldosterone were performed in baseline conditions and during progressive balloon inflation in the renal artery leading to stepwise 5% Pd decrements. Resistive index (RI) was computed as (1‐(End Diastolic V/Maximum Peak Systolic V))*100. A decrease of average peak flow velocity (APV) was observed when distal renal perfusion pressure decreased by 25% and was associated with activation of renin secretion. The RI decreased already for minimal changes in Pd/Pa ratio. In an animal model of unilateral graded RAS in the presence of a significant contralateral stenosis, a 25% decrease in perfusion pressure results in a significant decrease in distal renal flow, causing a more pronounced upregulation of renin secretion when compared to a model of graded unilateral RAS without contralateral significant RAS.